모바일 쇼핑몰 사용자환경의 디자인 심미성이 고객의 구매의도에 미치는 영향 - 정원진(Jung, Won-Jin) (대한경영학회지, 2012)
최근 들어서 스마트폰은 컴퓨팅 기능을 지닌 융복합화 된 모바일 통신 도구를 넘어 개인의 삶을 표현하는 수단이 되었고, 많은 사람들의 일상생활 일부분으로 자리 잡고 있다. 그러나 스마트폰의 작은 화면, 낮은 화질과 같은 제약조건은 스마트폰 기반 모바일 쇼핑몰과의 상호작용을 어렵게 만들고, 이는 모바일 쇼핑몰 고객의 감정이나 쇼핑몰에 대한 고객의 태도에 부정적 영향을 미칠 것으로 예상된다. 이에 본 연구는 스마트폰 환경에서 모바일 쇼핑몰 사용자환경의 디자인 심미성이 쇼핑몰 고객과의 상호작용이나 고객의 감성, 구매의도에 미치는 영향을 실증적으로 탐색해 보기로 하였다. 구조방정식을 이용한 자료 분석 결과 연구모형의 적합도는 양호하였다. 또한 연구모형의 변수들 간 경로분석 결과 쇼핑몰 사용자환경의 디자인 심미성에서 고객의 긍정 감성, 긍정 감성에서 구매의도, 상호작용에서 상호작용 만족도 등의 경로에서 통계적으로 유의한 결과를 확인 할 수 있었다. 그러나 쇼핑몰 사용자환경의 디자인 심미성과 상호작용, 상호작용 만족도와 고객의 긍정 감성, 상호작용 만족도와 구매의도와의 인과관계는 나타나지 않았다. 본 연구의 결과를 바탕으로 스마트폰, 상호작용, 사용자환경 디자인, 모바일 웹과 애플리케이션 개발 관련 연구 분야에 미약하나마 공헌 할 수 있게 되기를 기대해 본다. Recently, smartphones have become an integral part of people's daily lives. Now it is not difficult to find people using their smartphones not only to make conventional phone calls, but also to use a variety of applications for sending and receiving text messages, accessing Internet information as well as performing various tasks while on the go. The more smartphones grow in their capabilities, the more people want to carry them at all times. Even though people use smartphones in day-to-day life, there has been little empirical research on smartphones. Specifically, little empirical evidence and understanding of the impacts of visual aesthetic designs of mobile shopping malls on smartphone users' buying intentions has been documented. Therefore, the goals of this study are to examine 1) the direct effects of visual aesthetic designs of mobile shopping malls on customers' positive emotions and the indirectly effects through mediating variables, such as interaction and the satisfaction of interaction and 2) the effects of positive emotions on customers' buying intentions. In order to collect data, a survey was conducted. University students and practitioners who have visited mobile shopping malls recently with their smartphones participated in the survey. To analyse the data, Structural Equation Modeling (SEM) was used. The results of study showed that there was strong relationship between visual aesthetic designs of mobile shopping malls and smatphone users' positive emotions. Also, there was strong relationship between interaction with mobile shopping malls and the satisfaction of the interaction. However, there were no relationships between visual aesthetic designs of mobile shopping malls and interaction as well as between the satisfaction of interaction and smartphone users' positive emotions. Finally, this study found strong effects of positive emotions on customers' buying intentions. The findings of this study may imply that in order to increase smartphone users' buying intentions at mobile shopping malls, it is needed for mobile shopping malls to develop a m-commerce strategy for enhancing visual aesthetic designs of mobile shopping malls which in turn influence smartphone users' positive emotions. In order to validate the findings in this study, additional follow-up research is needed. KCI Citation Count: 8